STUDI PARTISIPASI POLITIK MASYARAKAT DALAM PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR RIAU PADA PUTARAN PERTAMA DI KECAMATAN PEKANBARU KOTA TAHUN 2013 - Armi, Ade Aditia; Ridwan, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This study aims to Determine why participation in District City Pekanbaru lower in the general election of Governor and Deputy Governor of Riau first round in 2013 and factors that influence people not Participate in the election. The concept of the theory used as a basis for analyzing community participation in Riau Governor Election 2013 is According to the theory of Milbrath that states a person's participation can be influenced by two factors: factors supporting and inhibiting factors. Based on the research that has been described, it is known that the factors that influence people's political participation is the type of work and amount of income. While the level of education does not really give effect to the low level of political participation in the District of Pekanbaru City. In addition, there are other factors that influence the low political participation of the community, such as the issue of domicile population, at the time of the election was out of town, and a lack of public confidence in the leader.Keywords: Factor Participation, Participation, Political, General Election